STUDI TENTANG FAKTOR RISIKO PENYEBAB PENYAKIT HIPERTENSI PADA PASIEN DI PUSKESMAS BIROBULI PALU - Wahyu; Sudirman; Lexy Kareba (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2023)
Hypertension is a public health problem in the world, as evidenced by the report on the prevalence of hypertension in Central Sulawesi according to a survey obtained from the district, there are 5 districts that have reported cases of hypertension, namely Bangkep 2,362 cases, Banggai District 8,642 cases, Poso District 1,496 cases. , and Palu City 10151 cases, in 2008 9,263 cases. The purpose of this study is to know the description of the risk factors that cause hypertension in patients at the Birobuli Health Center in Palu. This research is a descriptive research. The population is 36 people with a large sample or total population. The method of data collection is through questionnaires and observation, the data analysis used is univariate analysis. The results of the study found that out of 36 respondents based on a risky lifestyle there were 19 people (52.8%), who were not at risk there were 17 people (47.2%) and based on the results of the study according to the status of obesity who were fat there were 5 people (13, 9%), there were 3 people who were very obese (8.3%), and those who were normal were 28 people (77.8%). Based on the results of this study, it can be concluded that most of the risky lifestyle factors cause hypertension and a small proportion of obesity factors cause hypertension. patient life increases.